Innovation Improvement of the Elderly’s Quality of Life in Eastern Economic Corridor through the Folk Sports Wisdom - Somporn Songtrakul,; Wirat Sonchan,; Saralee Sonchan, (Journal of Educational Issues, 2024)
According to the increase of elderly population, the development of quality of life of the elderly is essential. So, the researcher decided to create innovations in improving the effective quality of life of the elderly in Eastern Economic Corridor through the folk sports wisdom. The sample was 90 elderly aged between 60-84 years old of the Ban Bueng Municipal elderly school and the elderly school of Map Phai Subdistrict Administration Organization, Ban Bueng district, Chonburi province, participated in innovative activities which created by the research team for a period of 5 weeks, 1 day for 3 hours. Statistical analysis included Frequency, Percentage, Mean, and Standard Deviation. The results showed that satisfaction on innovations in improving the effective quality of life of the elderly, in terms of location, equipment, and facilities, in terms of staffs organizing activities, and management and operations were at the highest level as well as the quality of life of the elderly after participating in activities, in terms of environment, physical and mental health was good while the social relations was at a moderate level. The elderly was satisfied with their own lives, worked well and got around by themselves, and built good social relationship among friends, and also chose age-appropriate recreational activities.